Volatiles of canned tuna fish and the effects of different parameters: A Review - Yetisen, Mehmet (FOOD ANALYTICA GROUP, 2021)
Tuna is one of the most important commercial fish species due to its economical and high nutritional values. There are many species of fish, which are eaten raw, used in home-cooked dishes and subject to various industrial activities, such as canning. The overall quality of fish and fishery products has become a major concern in fish industry in the world. Tuna processing methods mainly consist of freezing, cooking, smoking and canning after heat treatment like sterilization. The species used for canning are mainly yellowfin, skipjack and albacore tuna. The volatile components of tuna vary depending on the processing method. Different temperature conditions applied in canning productions significantly affect the volatile profiles. The aroma is one of the main indicators on which consumers judge the fish’s freshness. Fish flavour quality is changing rapidly according to the freshness of the product, and therefore, sensorial evaluation of the flavouring is used by consumers, researchers and the fishing industry as a whole to evaluate the quality of fish. Each species of fish has a tender and distinctive aroma, which can be influenced by processing technology, post production and storage methods. Volatile compounds derived from lipid are produced mainly by oxidative-enzymatic reactions and auto oxidation of lipids. Oxidation derived volatiles play crucial roles in the formation of overall fish aroma providing them a specific aroma character. Therefore, this review highlights the impact of various parameters on volatiles of canned tuna. Tuna is one of the most important commercial fish species due to its economical and high nutritional values. There are many species of fish, which are eaten raw, used in home-cooked dishes and subject to various industrial activities, such as canning. The overall quality of fish and fishery products has become a major concern in fish industry in the world. Tuna processing methods mainly consist of freezing, cooking, smoking and canning after heat treatment like sterilization. The species used for canning are mainly yellowfin, skipjack and albacore tuna. The volatile components of tuna vary depending on the processing method. Different temperature conditions applied in canning productions significantly affect the volatile profiles. The aroma is one of the main indicators on which consumers judge the fish’s freshness. Fish flavour quality is changing rapidly according to the freshness of the product, and therefore, sensorial evaluation of the flavouring is used by consumers, researchers and the fishing industry as a whole to evaluate the quality of fish. Each species of fish has a tender and distinctive aroma, which can be influenced by processing technology, post production and storage methods. Volatile compounds derived from lipid are produced mainly by oxidative-enzymatic reactions and auto oxidation of lipids. Oxidation derived volatiles play crucial roles in the formation of overall fish aroma providing them a specific aroma character. Therefore, this review highlights the impact of various parameters on volatiles of canned tuna.